Fabry–Perot interferometry in Weyl semi-metals. (17th December 2018) - Mukherjee, Dibya Kanti; Rao, Sumathi; Das, Sourin
Abstract: We show that the electrical transport across a minimal model for a time-reversal symmetry breaking Weyl semi-metal (WSM) involving two Weyl nodes can be interpreted as an interferometer in momentum space. The interference phase depends on the distance between the Weyl nodes ( ) and is anisotropic . It is further shown that a minimal inversion symmetry broken model for a WSM with four Weyl nodes effectively mimics a situation corresponding to having two copies of the interferometer due to the presence of an orbital pseudo-spin domain wall in momentum space. We point out that the value of the and consequently the interference phase can be tuned by driving the WSMs resulting in oscillations in the two terminal conductance measured in the direction of splitting of the Weyl nodes.